Handbook of research on managerial practices and disruptive innovation in Asia - Ordóñez de Pablos, Patricia, 1975-; Zhang, Xi, 1982-; Chui, Kwok Tai (Advances in business strategy and competitive advantage., 2020)
"This book explores emerging topics, challenges, and success factors in management, disruptive innovation, and inclusive economies in Asia"--